Coaching As a Method of The Skill Development in The Scope of Occupational Safety and Health - Paulina GAJEWSKA; Irena SZEWCZYK (Communications of International Proceedings, 2022)
A person learns and excels the skills all her or his life. A significant aspect of the development is an appropriate focus of the knowledge and skills, which in the vital way interact with the career. Fulfilling everyday duties is not based solely on using the acquired knowledge and skills; increasing one’s expertise and creating the concept of the continuous improvement is required. The objective of the article is to present theoretical considerations related to the functioning of system of the occupational training – for the paper, the occupational safety and health (OSH) training was chosen. The article presents the chosen tools used in the OSH training as well as innovative solutions. The question of coaching in the training related to this scope is also discussed. The broadest purpose of coaching is to stimulate the development of the occupational competencies through the perfecting the skills – firstly - leading to ensuring the high quality of the work and compliance with the working standards, and at the same time to the necessary innovativeness through the stimulation of the creativity. Providing the OSH training is not simple due to its topics. Presentation of the legal regulations often disturbs to activate the participants and to sustain their attention. The subject of such training causes that the language is perceived as uncommunicative by many participants. The objective of the article is to demonstrate that elements of coaching can be used during the OSH training so that its efficiency is higher and the stimulation of the job skills development is stronger.
Keywords: Safety and Health; Occupational Training; Coaching; Job Competencies